Budaya dan Heritage Kota Cirebon: Identitas, Komersialisasi dan Pariwisata - Lestari, Dian; Paryanto, Paryanto (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 23 No 2 (2023)DO - 10.24843/PJIIB.2023.v23.i02.p04, 2023)
This article describes the unique culture and historical heritage that is owned by the City of Cirebon, a city that is rich in identity and traditional traditions. The main focus of this article is on the role of commercialization and the tourism industry in preserving and promoting the culture and heritage of Cirebon City to tourists. This article also examines the relationship between art, architecture, traditional traditions and culinary arts and the identity of the city of Cirebon, and how these elements become the main attraction for tourists. Through an in-depth search, this article provides insight into the efforts made by the government and local communities to maintain and develop the cultural wealth and historical heritage of Cirebon City, while still considering the impact of commercialization on cultural authenticity and sustainability. This research is important for understanding the importance of cultural preservation and developing appropriate strategies for developing sustainable tourism that can provide economic and social benefits for the people of Cirebon City without compromising their identity and cultural integrity.